Postacute sequelae and adaptive immune responses in people with HIV recovering from SARS-COV-2 infection. (1st October 2022) - Peluso, Michael J.; Spinelli, Matthew A.; Deveau, Tyler-Marie; Forman, Carrie A.; Munter, Sadie E.; Mathur, Sujata; Tang, Alex F.; Lu, Scott; Goldberg, Sarah A.; Arreguin, Mireya I.; Hoh, Rebecca; Tai, Viva; et al.
Abstract : Background: Limited data are available on the long-term clinical and immunologic consequences of SARS-CoV-2 infection in people with HIV (PWH). Methods: We measured SARS-CoV-2-specific humoral and cellular responses in people with and without HIV recovering from COVID-19 ( n = 39 and n = 43, respectively) using binding antibody, surrogate virus neutralization, intracellular cytokine staining, and inflammatory marker assays. We identified individuals experiencing postacute sequelae of SARS-CoV-2 infection (PASC) and evaluated immunologic parameters. We used linear regression and generalized linear models to examine differences by HIV status in the magnitude of inflammatory and virus-specific antibody and T-cell responses, as well as differences in the prevalence of PASC. Results: Among PWH, we found broadly similar SARS-CoV-2-specific antibody and T-cell responses as compared with a well matched group of HIV-negative individuals. PWH had 70% lower relative levels of SARS-CoV-2-specific memory CD8 + T cells ( P = 0.007) and 53% higher relative levels of PD-1+ SARS-CoV-2-specific CD4 + T cells ( P = 0.007). Higher CD4 + /CD8 + ratio was associated with lower PD-1 expression on SARS-CoV-2-specific CD8 + T cells (0.34-fold effect, P = 0.02). HIV status was strongly associated with PASC (odds ratio 4.01, P = 0.008), and levels of certain inflammatory markers (IL-6, TNF-alpha, and IP-10) were associated with persistent symptoms. Conclusion: We identified potentially important differences in SARS-CoV-2-specific CD4 + and CD8 + T cells in PWH and HIV-negative participants that might have implications for long-term immunity conferred by natural infection. HIV status strongly predicted the presence of PASC. Larger and more detailed studies of PASC in PWH are urgently needed.